"Comportamiento agronómico de cuarenta y un cruces internacionales de cacao (Theobroma cacao L.) en la finca experimental la represa" - Herrera Tamayo, Nataly Lorena (2018)
The objective of this research was to evaluate the agronomic behavior of the interclonal crosses of cacao (Theobroma cacao L.), the same one that has a line in the Experimental Farm "La Represa" located in the Faita enclosure, km 7.5 of the Vía Quevedo - San Carlos, province of Los Ríos. A completely randomized design (DCA) was used, with forty-one treatments and two repetitions. Productive variables were evaluated (number of healthy ears and yield kg / ha / year), health variables (number of diseased ears), physical quality (length of grain, width of grain, thickness of loin, thickness of the furrow, index of ear, seed index and percentage of testa), cut test (percentage of fermentation) where the almonds were classified by their characteristic and an economic analysis where the total cost was established in each of the treatments. The results indicated that the treatments T2, T34 and T33 obtained the highest productive indices as well as presented the highest costs due to the high labor demand. Within the parameters of physical quality the treatment that stood out was the T16 with the highest seed index of 1.73; while T3 indicated the highest value in spine thickness and T8 in thickness of the plow with 2.40 and 1.59 respectively. When performing the cutting test according to the INEN-176 standard, the T31 with 92.50% entered the ASSPS category, which is the highest with 85% of the total fermentation. Key words: cocoa, crosses, agronomic behavior, production, physical quality